p130 And pRb in the Maintenance of Transient Quiescence of Mesenchymal Stem Cells - Boris Popov; Nikolai Petrov; Vladimir Ryabov; Igor Evsyukov (Stem Cells International)
An effective regulation of quiescence plays a key role in the differentiation, plasticity, and prevention of stem cells from becoming malignant. The state of quiescence is being controlled by the pRb family proteins which show overlapping functions in cell cycle regulation; however, their roles in controlling the proliferation of mesenchymal stem cells (MSCs) remain to be understood. This study investigated the regulation of transient quiescence using growth curves, proliferation assay, the cytometric evaluation of cell cycle, Western blotting, and the electromobility gel shift assay (EMSA) on synchronized MSCs of the C3H10Т1/2 and control cells with different statuses of pRb proteins. It has been found that functional steady-state level of p130 but not pRb plays a critical role for entering, exiting, and maintenance of transient quiescence in multipotent mesenchymal stem cells.